Evaluation of Pseudomonas aeruginosa toxin A in experimental rat burn wound sepsis. - Walker, H L (1979)
The search for methods to achieve control of Pseudomonas aeruginosa infection continues with the introduction of aluminum-absorbed toxoid developed from P. aeruginosa exotoxin. This toxoid induces significant titers of neutralizing and precipitating antibodies for toxin A when given with appropriate adjuvants. These experiments show that immunization with aluminum phosphate-absorbed toxoid failed to protect burned rats infected with P. aeruginosa. These and previous experiments show that active immunization with live P. aeruginosa provides good strain-specific protection in the same model. No cross-protection was demonstrated between strains of P. aeruginosa in these experiments.